Regulation of Surface Structure of [Au9Ag12(SAdm)4(Dppm)6Cl6](SbF6)3 Nanocluster via Alloying - Deng, Huijuan; Li, Xiaowu; Yan, Xiaoxun; Jin, Shan; Zhu, Manzhou (Frontiers in Chemistry, 2022)
Tailoring of specific sites on the nanocluster surface can tailor the properties of nanoclusters at the atomic level, for the in-depth understanding of structure and property relationship. In this work, we explore the regulation of surface structure of [Au9Ag12(SAdm)4(Dppm)6Cl6](SbF6)3 nanocluster via alloying. We successfully obtained the well-determined tri-metal [Au9Ag8@Cu4(SAdm)4(Dppm)6Cl6](SbF6)3 by the reaction of [Au9Ag12(SAdm)4(Dppm)6Cl6](SbF6)3 with the CuI(SAdm) complex precursor. X-ray crystallography identifies that the Cu dopants prioritily replace the position of the silver capped by Dppm ligand in the motif. The Cu doping has affected the optical properties of Au9Ag12 alloy nanocluster. DPV spectra, CD spectra and stability tests suggest that the regulation of surface structure via Cu alloying changes the electronic structure, thereby affecting the electrochemical properties, which provides insight into the regulation of surface structure of [Au9Ag12(SAdm)4(Dppm)6Cl6](SbF6)3via alloying.